Blended learning models in Ugandan higher business education: best practices and lessons learned - Mahadih Kyambade; Rashid Kisseka; Afulah Namatovu (Cogent Education)
This study explored the implementation of blended learning models in higher business education, focusing on identifying best practices and lessons learned from key stakeholders. As blended learning becomes increasingly vital in modern pedagogy, business schools are challenged to design effective hybrid models that balance flexibility, engagement and academic rigor. Adopting a qualitative study approach, data were collected through semi-structured interviews with 24 staff, instructional designers and undergraduate students in selected Ugandan business schools. Thematic analysis was conducted using NVivo version 12 software, revealing six emergent themes including best practices in blended course design, effective instructional strategies, institutional support and policies, technological and pedagogical challenges, stakeholder experiences (staff and students) and lessons learned over time. Participants emphasized the importance of deliberate course planning, continuous faculty training, adaptive use of technology and responsive institutional frameworks in driving successful blended learning outcomes. At the same time, challenges, like digital literacy gaps, inconsistent connectivity and resistance to change were noted. Findings provide insights into how blended learning can be better structured and supported in higher business education. They underscore the need for context-specific strategies that align pedagogy, technology and institutional policies to enhance student engagement and academic success in both physical and virtual learning environments.